KINERJA KOMISI PEMILIHAN UMUM DAERAH (KPUD) DALAM MENSUKSESKAN PEMILIHAN UMUM KEPALA DAERAH HULU SUNGAI UTARA PERIODE 2012-2017 - Nurfajrina, Siti (Pendidikan Kewarganegaraan, 2014)
Siti Nurfajrina, 2013. The Achievement of General Election Commission (KPUD) in Suceeding Hulu Sungai Utara (HSU)Regent Election Years 2012-2017. Sarjanaâs Thesis of Citizenship Department. Social Knowledge of FKIP Lambung Mangkurat University. Advisor (I) Wahyu, (II) Harpani Matnuh. General election had strategical role in the process of develoving democratic nation where societies were involedin the process of voting of political desicions by using their political rights and obligations as responsible citizen. Interrelated to the importance of general election in the pocess of democracy in a country, so it was important to manifest the really-based-democratic-values general election and support the democracy it self. So that there would be optimum achievement of the general commissions comitee to manifest honest, free and fair. But in Regent General Election (Pemilukada) 2012 Kabupaten Hulu Sungai Utara that was held by KPUD HSU exposing accusation and dissapointment of General Election participants to KPUD HSU. The purpose of this study was to analyze the achievement KPUD HSU monitored by 5 aspects, that is, productivity, responsivity, responsibility and accpuntability.The methode of this research is qualitative approach, and to determine data source, this study used purposive sampling. Collecting data technique was conducted by observing, semi-structural interviewing, and documentation. Data analysis was conducted by reducing,Â  providing and concluding the data.The reseacrh result sowed (1) The Productivity of KPUD Kabupaten HSU can be stated to be fair optimum. (2) The quality of service KPUD HSU in serving the participants in Regent General Election (Pemilukada) 2012 was categorized as the good one. (3) Responsivity KPUD HSU in conducting Pemilukada 2012 was stated optimum. (4) Responsibility of KPUD HSU is less optimum in vertification stage. (5)Â  The accountabilty of KPUD HSU in conducting Pemilukada 2012 was optimum as well. Based on the research result, itÂ  was suggested that (1) KPUD HSU should increase the understanding about Regent General Election to the society. (2) The KPUD HSUshould increase the quality of service tio the society and provide more complaint medium. (3) The KPUD HSU is expected to pvercome the problem well. (4)Â  The KPUD HSU should prepare in advance to conduct th trainings in order to undertand the stage of regent general election process. (5) The KPUD HSU should give more attention to the officials or members of KPUD like motivation, work ethic, and the model in develoving the quality of their workers.Keywords: KPUD HSU, Achievement, Regent Election